Decellularized Adipose Tissue Hydrogel Promotes Bone Regeneration in Critical-Sized Mouse Femoral Defect Model - Mohiuddin, Omair A.; Campbell, Brett; Poche, J. Nick; Ma, Michelle; Rogers, Emma; Gaupp, Dina; Harrison, Mark A. A.; Bunnell, Bruce A.; Hayes, Daniel J.; Gimble, Jeffrey M. (Frontiers in Bioengineering and Biotechnology, 2019)
Critical-sized bone defects fail to heal and often cause non-union. Standard treatments employ autologous bone grafting, which can cause donor tissue loss/pain. Although several scaffold types can enhance bone regeneration, multiple factors limit their level of success. To address this issue, this study evaluated a novel decellularized human adipose tissue (DAT) hydrogel as an alternative. In this study, DAT hydrogel alone, or in combination with adipose-derived stromal/stem cells (ASC), osteo-induced ASCs (OIASC), and hydroxyapatite were tested for their ability to mediate repair of a critical-sized (3 mm) femoral defect created in C57BL/6 mice. Micro-computed tomography results showed that all DAT hydrogel treated groups significantly enhanced bone regeneration, with OIASC + hydroxyapatite treated group displaying the most robust bone regeneration. Histological analyses revealed that all treatments resulted in significantly higher tissue areas with the relative mineralized tissue area significantly increased at 12 weeks; however, cartilaginous content was lowest among treatment groups with OIASC. Immunohistochemical analyses showed that DAT hydrogel enhanced collagen I and osteopontin expression, while the addition of OIASCs to the hydrogel reduced collagen II levels. Thus, DAT hydrogel promotes bone regeneration in a critical-sized femoral defect model that is further enhanced in the presence of OIASCs and hydroxyapatite.